A rare variation in the formation of the lower trunk of the brachial plexus its embryological basis and clinical importance - a case report - Satyanarayana, N; Guha, R; Sunitha, P; Reddy, GN; Praveen, G; Datta, AK (Journal of College of Medical Sciences-Nepal, 2012)
Brachial plexus is the plexus of nerves, that supplies the upper limb.Variations in the branches of brachial plexus are common but variations in the roots and trunks are very rare. Here, we report one of the such rare variations in the formations of the lower trunk of the brachial plexus in the right upper limb of a male cadaver. In the present case the lower trunk was formed by the union of ventral rami of C7,C8 and T1 nerve roots. The middle trunk was absent. Upper trunk formation was normal. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 49-52 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6727